Peran Program Lisan Arab Dalam Mengembangkan Kemampuan Berbahasa Arab Bagi Mahasiswa Baru Pendidikan Bahasa Arab UPI - Az-Zahwa Tri Novita; Farida Yumna Nabilah; Salma Aulia Rahmadizkra; Muhammad Royyan; Muhammad Alghifari Binadibu; Ahmad Fu’adin (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research is aimed at finding out and analyzing the role of the Oral Arabic program in developing Arabic language skills for new students of the Arabic Language Education study program at the Indonesian University of Education. This program was held based on the problem of differences in the backgrounds of students, some of whom have not or have never studied Arabic, which hinders these students from understanding the learning in class. The research method used in this research is descriptive qualitative. The resource person in this research is one of the new students who is taking part in the Oral Arabic program. From this research, data was obtained regarding the Arabic Oral Program, such as the number of students and educators, the purpose of the program, the teaching materials used, and the obstacles faced during the learning process.